(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Osteoma of the mandible are reported to be uncommon in literature. They generally are asymptomatic, and discovered on routine clinical examination. However, with gradual increase in size they may cause ulceration of the overlying mucosa and cause difficulty in fabrication of the prosthesis. Surgical intervention for management of these entities is an option which is reserved for symptomatic cases.